تلوث مكبات النفايات الصلبة على تلوث حامل الصخور الكربوناتية في حوض الأبرش ( الساحل السوري ) - كابر, يوسف (Latakia University Journal -Basic Sciences Series, 2018)
إن الدراسة التي قمنا بها حول تأثير أربعة مكبات مكشوفة فوق مناطق التغذية للحامل الكربوناتي, سمحت لنا باستخلاص النتائج التالية الآتية: تقدر كمية النفايات الصلبة في المكبات المدروسة بـ 20000 طنا/السنة, وسوف تزداد تدريجياً بفعل التنمية الاجتماعية والاقتصادية في منطقة الدراسة. تُسهم الهطولات المتباعدة خلال الأشهر الرطبة في تنشيط الرشاحة الخارجة من المكبات المكشوفة, وتسبب زيادة انتشار التلوث، وخاصة في النظام المائي الجوفي للطبقات العليا للحامل الصخري الكارستي والمتشقق. بيّنت نتائج التحاليل الكيميائية الدورية لـ 32 عينة مأخوذة من مياه جوفية لآبار وينابيع في أماكن متفرقة للحامل الصخري، ارتباط التركيب الكيميائي للعينات المدروسة بالوسط الجيولوجي الكربوناتي خلال الأشهر الجافة، بينما تتأثر نوعية المياه الجوفية في المستويات العليا للحامل بالنفايات الصلبة أثناء الأشهر الرطبة, حيث تزداد قيم معظم الشوارد, وتظهر بعض المعادن الثقيلة, وهذا مؤشر حقيقي للتلوث الكيميائي، ولكن الينابيع الغزيرة مازالت نوعيتها جيدة باعتبارها نقاط صرف خاصة بالجريان الإقليمي للمياه الجوفية العميقة التي تدخل الطبقات السفلية للنظام الجيولوجي من المناطق المجاورة لحوض الأبرش. أشارت الخريطة البيزومتريه لعام 2005 الى احتمال انتشار التلوث حسب الاتجاهات المسيطرة لحركة المياه الجوفية خاصّةً إلى الأجزاء الغربية للحامل الصخري الكربوناتي. The study of the impact of the four open landfills on a carbonate aquifer in the Abrash basin leads to the following conclusions. The quantity of solid wastes is about 20000 tons per year. It increases gradually by the development of socioeconomic activities in the area. The separate precipitations during rainy months give rise to lixiviation water that escapes from open landfills and contributes to increasing ground water contamination, especially in upper parts of karstic and fractured carbonate aquifer system. The results of 32 periodical chemical analyses showed that there is a relationship between sample composition of springs and wells with geological medium during the dry months. On the other hand, the quality of the ground water in the upper strata is affected by the solid wastes during the rainy months, when most of the ions increase and some heavy metals appear. It is a real index of chemical contamination by solid wastes. Springs with high flow in the lower strata of carbonate aquifer system are steel potable. They are considered as charge in deep regional ground water flow, that enters the system from outside the Abrash basin. The piezometric map refers the possibility of contamination diffusion with the same direction of ground water that predominates the flow especially toward the western parts of carbonate aquifer.